2022
DOI: 10.3389/fcvm.2022.910898
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of pulse-induced contour cardiac output monitoring in elderly patients with coronary artery disease and severe heart failure at coronary care units

Abstract: BackgroundThe optimal treatment for elderly patients with severe heart failure depends on the accurate assessment of their hemodynamic status. Due to its less invasive nature, the safety and efficacy of invasive pulse-induced contour cardiac output (PiCCO)-based hemodynamic monitoring remains uncertain.MethodsThis was a prospective observational study. Between January 2016 and July 2020, 190 elderly patients with severe heart failure were consecutively enrolled. The PiCCO group (89 patients) and non-invasive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The objective of the optimization first needs to be determined. As the optimization objectives for LPM individualization, the haemodynamic indicators should be able to be used to observe the acute responses of EECP through noninvasive clinical measurement 25–27 . In clinical EECP therapy, relevant and easily measurable indicators are usually brachial aortic pressure (BAP), CO, and ICAF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the optimization first needs to be determined. As the optimization objectives for LPM individualization, the haemodynamic indicators should be able to be used to observe the acute responses of EECP through noninvasive clinical measurement 25–27 . In clinical EECP therapy, relevant and easily measurable indicators are usually brachial aortic pressure (BAP), CO, and ICAF.…”
Section: Methodsmentioning
confidence: 99%
“…As the optimization objectives for LPM individualization, the haemodynamic indicators should be able to be used to observe the acute responses of EECP through noninvasive clinical measurement. [25][26][27] In clinical EECP therapy, relevant and easily measurable indicators are usually brachial aortic pressure (BAP), CO, and ICAF. BAP and CO can be used to evaluate the therapeutic effect of EECP on coronary heart disease, while ICAF can be used to evaluate the therapeutic effect on stroke.…”
Section: Patient-specific Global Haemodynamic Simulation Of Eecpmentioning
confidence: 99%
“…pre-ejection period (PEP), left ventricular ejection time (LVET)] are measured by a non-invasive haemodynamic monitoring technique -Task Force Monitor (TFM). Such techniques are considered an alternative to invasive haemodynamic monitoring in intensive care units [16]. In the authors' opinion, this is the first study that evaluates heart contractility parameters after acute sleep fragmentation in laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such monitoring has been successful and proved to be useful in a group of fragile patients suffering from severe heart disease. While PAP is known as an independent risk factor for one-month mortality among these patients, it has been shown that monitoring as in PICCO, where ELWI is estimated, may enable an accurate decision in regard to fluid therapy as well as antidiuretic drugs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%